MENGATASI KENAKALAN REMAJA DI KELUARGA BROKEN HOME MELALUI PENDIDIKAN AGAMA ISLAM - Nuraidah, Syifa; Wahid, Annisa (ILJ: Islamic Learning Journal, 2024)
This research aims to explore the role of Islamic religious education in addressing juvenile delinquency among adolescents from broken homes through a literature review.The research methodology employed is a literature review, collecting and analyzing various relevant literature, scholarly articles, books, and other sources. The gathered data is analyzed using a descriptive and synthesis approach to understand the role of Islamic religious education in addressing juvenile delinquency in broken homes. These findings provide insights into the role of Islamic religious education in addressing juvenile delinquency in broken homes through previous research. The findings of this research indicate that Islamic religious education can have a significant role in addressing juvenile delinquency among adolescents from broken homes. The literature suggests that Islamic religious education provides a strong moral and ethical framework for adolescents, helps them develop a stable identity, and provides guidance in facing challenges and trials in their daily lives.